Pelatihan Guru dalam Menerapkan Metode Storytelling Berbasis Nilai Moral untuk Meningkatkan Karakter Siswa di Sekolah Dasar - Lia Rismawati; Made Ayu Pransisca; Muh. Jaelani Al-Pansori (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2023)
This training program aims to enhance teachers' understanding and skills in implementing storytelling methods in learning, thereby improving students' comprehension of moral values. The methods employed in this program include observation, interviews with teachers, and the distribution of questionnaires to students to evaluate the effectiveness of storytelling implementation. This activity was conducted at SD-SMP Satap Sambelia, East Lombok Regency. The evaluation results indicate a significant improvement in teachers' understanding and storytelling skills, along with a positive impact on students' learning interest, comprehension of moral values, and changes in attitudes and behavior. Furthermore, storytelling has been proven to enhance students' social interactions and communication skills in the classroom. Therefore, storytelling can be adopted as a primary method for character education in elementary schools, supported by ongoing teacher training and the development of more innovative learning media.